Subjectivities of Suitability: ‘Intimate Aspirations’ in an Engineering College - Nandini Hebbar N. (South Asia Multidisciplinary Academic Journal)
In this paper, I attempt to capture the “intimate aspirations” of young women as they emerge in the narratives of their relationships in college, their marriage strategies and negotiations in an engineering college in Tamil Nadu. Given the kind of surveillance and the disciplinary mechanisms implemented by college authorities, the engineering college is not just a site of youth sociality, but emerges in politically significant ways to influence students’ “intimate aspirations.” Relationship trajectories develop on a terrain of intersectionality between caste and gender as students explore possible marriage through the possibility of being able to “convince” parents. While potentially indicating shifts in endogamy, what these “choices” conclusively show is the crafting of suitable subjectivities within the realm of the acceptable. Young women emphasize their professional and academic achievements, and those of their partners, in ways that complement existing status, in order to highlight a suitable marriage. I argue that such responses show the concomitant ways in which caste and gender are produced.